Nuovi paesaggi e aree minerarie dismesse (2013)
This work discusses the processes and dynamics of the landscapes of the mining industry, of the degraded areas, and of their possibilities for redevelopment through the creation of "new landscapes". The case of abandoned mining areas is seen in the context of the three phases of landscape transformation (previous, contemporary and subsequent to the mining activity), and in the context of the expanse of the regions affected by the phenomenon. The latter led to the hypothesis that the territory enhancement project should be placed within a complex system, whose main features are widespread interventions involving and intercepting both new and consolidated landscape networks.